Development and Women's Work in Kerala Interactions and Paradoxes - Rachel Kumar (Economic and Political Weekly December 17-24, 1994, 1994)
Notwithstanding the various measurement shortcomings in existing secondary estimates, the pattern of falling female workforce participation rates in Kerala persists and may well be a reflection of the real situation. This article examines various demographic, social and economic factors which may have contributed to the observed trends